Single nucleotide polymorphisms in IL1B and the risk of acute coronary syndrome: a Danish case-cohort study. - Jakob Gerhard Stegger; Erik Berg Schmidt; Anne Tjønneland; Tine Iskov Kopp; Thorkild I A Sørensen; Ulla Vogel; Kim Overvad (PLoS ONE, 2012)
Background Interleukin-1B (IL-1B) is a key pro-inflammatory cytokine that has been associated with the development of atherosclerosis and myocardial infarction. However, the prospective associations between functional single nucleotide polymorphisms (SNPs) in IL1B and incident acute coronary syndrome (ACS) have not been thoroughly investigated. The aims of this study were to examine the associations between individual SNPs in and SNP haplotypes of the promoter region of IL1B and incident ACS in a prospective study. Furthermore, we wanted to explore potential interactions with other risk factors for ACS on an additive scale. Methodology/principal findings The present study was based on the Danish prospective study Diet, Cancer and Health comprising more than 57 000 participants aged 50-64 at baseline. During a median follow-up of 7.2 years we identified 989 cases of incident ACS (755 men and 234 women). All cases were validated by review of medical records, and information on covariates was collected by study technicians. The study was conducted according to a case-cohort study design including ACS cases and a sex-stratified sub cohort of 1663 participants drawn randomly from the entire cohort. Weighted Cox proportional hazard models with age as time axis were used in the statistical analyses. Individual IL1B SNPs, SNP haplotypes, or haplotype combinations were not significantly associated with incident ACS, and, likewise, we found no evidence of interaction on an additive scale between IL1B haplotypes and risk factors, respectively. Conclusions/significance Genetic variation in the promoter region of IL1B may not be associated with incident ACS in men or women above the age of 50 years.